2019
DOI: 10.1186/s42269-019-0060-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sulfur dust application on the abundance of two important coccinellid predators in marrow fields

Abstract: Background: For the sake of environmental safety, many sulfur formulations were recommended in many Integrated Pest Management (IPM) programs to protect, particularly, edible vegetables and fruit trees from insect and mite pests as well as plant pathogenic diseases. Such formulations, at the recommended application rates, proved to be safer to mammals. Regarding their safety to beneficial arthropods, diversified results were reported. This study was designed to investigate and evaluate the impact of sulfur for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…Adult predators escaping from treated plants into other clean plants are either adjacent to the treated plots or moves to other far plants. This result was in agreement with that reported by Matter et al (2018Matter et al ( , 2019 and Gesraha and Ebeid (2019).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Adult predators escaping from treated plants into other clean plants are either adjacent to the treated plots or moves to other far plants. This result was in agreement with that reported by Matter et al (2018Matter et al ( , 2019 and Gesraha and Ebeid (2019).…”
Section: Resultssupporting
confidence: 94%
“…In addition, results explain that the difference between the sprayed tested plants was significantly affected by the mean numbers of the recorded predatory adults. Where marrow plant was heavily invaded by different insect and/or mite pests consequently comprised a large number of different examined predators, these findings agreed with that reported by Matter et al (2018Matter et al ( , 2019 and Gesraha and Ebeid (2019).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The control of the red mite is achieved by pesticides usage, mineral oils, and aerial sulfur applications (Ripa and Larral, 2008). However, some studies have reported susceptibility and mortality of Stethorus punctillum, S. punctum picipes, and S. nigripes (Coleoptera: Coccinellidae) to pesticides and sulfur (Hoy, 2011;Gesraha and Ebeid, 2019), making challenging their incorporation into integrated pest management (IPM) programs. Hence, new predators adapted to different prey availability and pesticides tolerance are required to avoid foliar damage in avocado plants.…”
Section: Introductionmentioning
confidence: 99%
“…Sulphur is necessary for the biosynthesis of some amino acids (cysteine, cystine, and methionine), which are important components of proteins (Mukwevho et al, 2014). Sulphur also aids in winter hardiness and drought tolerance, as well as the prevention of insect pests and disease (Hasanuzzaman et al, 2018b;Gesraha and Ebeid, 2019). To keep the importance of macronutrients and sulphur on cauliflower, this study was conducted to optimize the best suitable dose of NPK and sulphur for the maximum growth, yield and quality of cauliflower.…”
Section: Introductionmentioning
confidence: 99%